Effect of cultivars and split application of nitrogen at the different growth stages on yield and its component of bread wheat (Triticum aes-tivum L.) under rain-fed conditions in Kurdistan, Iraq - Hassan, Ali Muhammed; Noori, Shang Haseeb Abdulqader (Journal of Kerbala for Agricultural Sciences, 2023)
To investigate the best N fertilizer application regime for the environment and the economy. Therefore, a field experiment was conducted for one year (2020–2021) under the rain-fed condition at two locations in the Sulaimani region; Qlyasan research field of the College of Agriculture Engineering University of Sulaimani and the Kanipanka research station in the Sharazoor valley to determine the effect of the application of 120 kg ha-1 N in four split doses (T6) at four growing stages, sowing, tillering, booting, and spiking, respectively. Were T1 (60 kg ha-1 N at sowing, 60 kg ha-1 N at tillering) used as a control, T2 (60 kg ha-1 N at sowing, 30 kg ha-1 N at tillering, 30 kg ha-1 N at booting), T3 (60 kg ha-1 N at sowing, 30 kg ha-1 N at tillering, 30 kg ha-1 N at spiking), T4 (60 kg ha-1 N at sowing, 20 kg ha-1 N at tillering, 20 kg ha-1 N booting, 20 kg ha-1 N at spiking), T5 (40 kg ha-1 N at sowing,30 kg ha-1 N at tillering, 30 kg ha-1 N at booting, 20 kg N ha-1 N at spiking) and T6 (40 kg ha-1 N at sowing, 40 kg ha-1 N at tillering, 40 kg ha-1 N at booting) and their effect on grain yield and it’s components of bread wheat cultivars (Adana-99, Hawler-4, and Sulaimani-2). A split plot arrangement within Randomimized Complete Block Design with three replicates was used. The possible comparison among the means was calculated following the Duncan test at a significant level of 0.05. As part of grain yield, no. of spikes m-2, no. of grains.spike, thousand-grain weight (g) (TGW), grain yield ton ha-1 (GY), biological yield ton ha-1 (BY), and Harvest Index (H.I) were all calculated. As the average of both locations of the results showed that the impact of Cultivars on agronomic traits was significant, Sulaimani-2 produced the maximum values for all characters, with the exception of (TGW) and (H.I), which were provided by Hawler-4. All the bread wheat characters were significantly influenced by the time of application of nitrogen, where T5 produced the maximum value for all characters with the exception no. of spike m-2, where T6 had the ultimate value. The no. of spikes m-2 had a significant effect on the T4, and T5 study characters. Based on what we’ve found, the best combination is Sulaimani-2 with T6 and T5 except in Qlyasan location with T6 only when rain is guaranteed. This increases both the yield and its components.